Role of nerve block as a diagnostic tool in pudendal nerve entrapment. Issue 6 (15th May 2019) - Dickson, Edward; Higgins, Patrick; Sehgal, Rishabh; Gorissen, Kim; Jones, Oliver; Cunningham, Chris; Hogan, Aisling M.; Lindsey, Ian
Abstract : Background: Pudendal nerve entrapment is a disabling condition which is difficult to diagnose and treat. Nantes criteria include the requirement of positive anaesthetic pudendal nerve block that is widely used to allow identification of patients likely to benefit from the definitive but invasive pudendal nerve release. This study aimed to determine if pudendal nerve blockade under general anaesthesia could diagnose and temporarily treat pudendal nerve entrapment in patients suffering from chronic pelvic/perineal pain and/or organ dysfunction. Methods: This retrospective analysis of a prospectively maintained database examined the outcomes of all recipients of diagnostic pudendal nerve block in a quaternary referral centre between 2012 and 2017. Primary outcome was relief of perineal pain (transient or permanent). Secondary outcomes were demographics, referral patterns for definitive procedure and complication rates. Statistical analysis was performed using SPSS v 24. Results: A total of 77 patients were included in the study. Mean age was 57.27 ± 13.55 years. Majority were females ( n = 62, 80.5%). Relief of pain was experienced by 47 of 76 (68.1%) patients after initial injection. Complication rate of injection was 3.9% ( n = 3) which in all cases was unilateral lower limb paraesthesia. Of the 37 patients (52.9%) referred, 20 underwent surgical decompression with 12 (60%) being successful. Conclusion: Pudendal nerve injection is a safe and simple procedure that can provide accurate diagnosis and transient relief from this chronic and debilitating problem. This technique helps to isolate patients suitable for pudendal nerve decompression which offers high success rates.